2001
DOI: 10.1046/j.0014-2956.2001.02493.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interaction of 16S rRNA and cytoplasmic membrane with the C-terminal part of the Streptococcus pneumoniae Era GTPase

Abstract: Era, an essential GTPase, plays a regulatory role in several cellular processes. The Era protein of Streptococcus pneumoniae has recently been shown to bind to 16S rRNA and the cytoplasmic membrane. However, exact locations of Era responsible for RNA-and membrane-binding were unknown. To identify the regions in Era that interact with the RNA and membrane, the C-terminal part of S. pneumoniae Era was systematically deleted while the N-terminal part, responsible for the GTPase activity of the protein, was kept i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 18 publications
(74 reference statements)
1
21
0
Order By: Relevance
“…It has been suggested that Era might play a role in the control of the cell cycle (8,9,12). It has also been shown that Era interacts with 16S rRNA and the 30S ribosomal subunit (13,24,29). Furthermore, 16S rRNA dimethyltransferase has been demonstrated to suppress a cold-sensitive mutant of Era E200K when expressed in a multicopy plasmid (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that Era might play a role in the control of the cell cycle (8,9,12). It has also been shown that Era interacts with 16S rRNA and the 30S ribosomal subunit (13,24,29). Furthermore, 16S rRNA dimethyltransferase has been demonstrated to suppress a cold-sensitive mutant of Era E200K when expressed in a multicopy plasmid (19).…”
mentioning
confidence: 99%
“…Era consists of an N-terminal GTP-binding domain and a conserved C-terminal domain that contains a putative KH domain (10) capable of binding RNA (13,17,24). The cellular function of Era still remains elusive.…”
mentioning
confidence: 99%
“…Indeed, RNA-binding activity of bacterial ERA has previously been reported (Meier et al, 1999(Meier et al, , 2000Sayed et al, 1999;Hang et al, 2001). We have also demonstrated that mammalian ERA has RNA-binding activity, which is contributed by the KH-like domain (Akiyama et al, 2001).…”
Section: Introductionmentioning
confidence: 51%
“…Possible requirement of RNA-binding activity for the regulation of cell cycle by vertebrate ERA It has been reported that eukaryotic ERA, as well as prokaryotic ERA, is an RNA-binding protein (Meier et al, 1999;Sayed et al, 1999;Akiyama et al, 2001;Hang et al, 2001). As shown in Figure 4d, the phenotype of the ERA-null cells was not reversed by the expression of the Hs1-375 mutant, which possesses no RNA-binding activity.…”
Section: Function Of Vertebrate Era On Cell Cycle Progression Is Distmentioning
confidence: 69%
“…The importance of the KH domain has been demonstrated for Era, since truncated Era genes were unable to complement an E. coli mutant strain defective in Era expression [29]. Likewise, the KH domain of EngA has been shown to be involved in the binding of EngA to the 30S ribosomal subunit [30].…”
Section: Obtention Of Ysxc Mutantsmentioning
confidence: 99%